Oh, Harry! - Kumin, Maxine, 1925-2014 (Roaring Brook Press, 2011)
Harry the Horse excels at calming skittish equines in Adams & Son's show-horse barn, but he faces a different challenge when mischievous six-year-old Algernon Adams the Third arrives.